Perception and flagging of loanwords – A diachronic case-study of Māori loanwords in New Zealand English. (2019) - Levendis, Katharine; Calude, Andreea
Abstract: This paper combines a quantitative and qualitative analysis of a diachronic corpus of New Zealand newspapers built to analyse the use of Māori loanwords in New Zealand English. We report findings in relation to flagging (marking of loanwords as being foreign material in a given language) and show that it is (weakly) predicated by frequency-of-use and by semantic category of the loanword (core loans are flagged more than cultural ones), but not by listedness. Alongside this trend, we note that perceptions of writers using the words vary enormously in regard to which loans are integrated and familiar, matching neither listedness nor frequency-of-use patterns. This indicates that in NZE, loanword use remains strongly tied up with socio-political identity and language ideology, rather than rooted in linguistic factors (such as, bilingualism or filling in lexical gaps). Highlights: Flagging is not only merely a linguistic reflex. Flagging is also a sociolinguistic tool that enables speakers to consciously spread new incoming loanwords. Flagging allows speakers to refresh the use of previously existing (sometimes already listed) loanwords. Flagging is mediated by speaker perception and speaker attitude. It is therefore not necessarily an accurate barometer for the degree of acceptance/integration of a given loanword in a RL. This is of particular importance to language contact scenarios of asymmetrical lexical movement.